(untitled) (E Conference Zone, 2022)
In developing society, our country requires learning skills that could help it keep pace with the development of science and technology. Educational systems in a community and consequently education will not be able to separate from other social institutions, national and international interactions widely known in the global village. Education in the twenty-first century is the center from which all changes and developments arise. Information technology in education needs a culture. This culture needs to be learned along with the use of hardware resources. The system needs to be educated to use information technology; otherwise, purchase and transfer of technology and investment will be nothing but wasting resources. Although these technologies are not impartial in any sense they should be used as means for communicating information, in the existing social structures. However since the process of change and transformation is in the nature of human social institutions, the educational system is also prone to some alterations. But the fundamental problem is that what strategies should be adopted so that education systems in developing countries do not only follow developed countries but grow and progress base on their own needs in the path of progress. In this paper, after explanation about the role of information technology and its place in education in underdeveloped countries and Iran, a discussion is presented on how to enter the field of information society and how to use information technologies.